Monoteisme Kekristenan dan Para Penantangnya - Wells, Paul (Verbum Christi: Jurnal Teologi Reformed Injili, 2022)
The Christian Trinity is a diversified form of monotheistic faith, since the apostolic faith is rooted in the Old Testament confession, to which Jesus adhered: “the Lord our God, the Lord is one”. Christianity never renounced monotheism, but build on that basis. Recently theologians (including Jürgen Moltmann) have been critical of Christian monotheism which has overshadowed trinitarianism from Thomas Aquinas onwards. It means that today many Christian believers are practical monotheists and the Trinity has little place in spirituality. But this is not the main challenge to Christian monotheism in the global world context of today